(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This study aims to shed light on one of the aspects of Emirati novels, particularly the transformations that have emerged due to the changes undergone by the Emirati society in the 21st century. The study focuses on the element of space to highlight, critique, and analyze these transformations, since space is a crucial element in the narrative discourse. Through space, the reader can unveil the hidden meanings within the text, and a critical analysis of space allows the reader to comprehend the narrative content and its intricacies. Additionally, space often reflects the influence of the environment on the writer’s psyche and emotions, which is what we aimed to address in this study. We were able to achieve this through the examination of one of the most prominent novels in the Emirati literary scene, namely: Rā’iḥa Al-Janzabīl [The Scent of Ginger] by the novelist Ṣalḥa ‘Ubayd Ġābish.